Effect of CO2 in the oxidative dehydrogenation reaction of propane over Cr/ZrO2 catalysts - Oliveira, Joao F. S. de; Volanti, Diogo P. [UNESP]; Bueno, Jose M. C.; Ferreira, Adriana P. (Elsevier B.V., 2018)
Investigation was made on the effect of chromium content, and method of hydrothermal preparation of Cr/ZrO2 catalysts on their catalytic properties for CO2 oxidative dehydrogenation of propane (ODP). The catalysts were characterized by nitrogen physisorption, X-ray diffraction, Raman spectroscopy, and temperature programmed reduction and desorption of CO2 (TPD-CO2). The Cr/ZrO2 catalysts containing various chromium contents between 2.5 and 15 wt.% of Cr were prepared by conventional and microwave-assisted hydrothermal methods. Tetragonal ZrO2 was formed, with higher Cr contents, and smaller crystallite sizes obtained using the microwave -assisted method. The relationship between selectivity to propene and propane conversion suggested that independent of the preparation method, the catalytic properties could be classified in two groups, with low and high chromium contents. The TPD-CO2 results showed that a fraction of the CO2 was desorbed at temperatures higher than 500 degrees C, with simultaneous reduction of Cr(VI) species. The presence of CO2 in the reactants caused strong decreases of activity, selectivity, and yield towards propene. These results suggested that CO2 adsorbed strongly on the chromium oxide active sites for dehydrogenation of propane. The Cr/ZrO2 catalysts were active and selective for dehydrogenation of propane in the absence of CO2 (CDP), and became deactivated with time on stream. The activity was reestablished by thermal treatment with CO2 or O-2 after deactivation in CDP catalytic cycles, with the activity always being reestablished by treatment in O-2. The deactivation occurred by reduction of Cr(VI) species and by deposition of carbonaceous species produced in oligomerization reactions.
Keywords: Chromium-zirconium oxides; Microwave; Oxidative dehydrogenation of propane; CO2; Basic sites